-8(-5p+4)-6=-8p+10

Simple and best practice solution for -8(-5p+4)-6=-8p+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(-5p+4)-6=-8p+10 equation:


Simplifying
-8(-5p + 4) + -6 = -8p + 10

Reorder the terms:
-8(4 + -5p) + -6 = -8p + 10
(4 * -8 + -5p * -8) + -6 = -8p + 10
(-32 + 40p) + -6 = -8p + 10

Reorder the terms:
-32 + -6 + 40p = -8p + 10

Combine like terms: -32 + -6 = -38
-38 + 40p = -8p + 10

Reorder the terms:
-38 + 40p = 10 + -8p

Solving
-38 + 40p = 10 + -8p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '8p' to each side of the equation.
-38 + 40p + 8p = 10 + -8p + 8p

Combine like terms: 40p + 8p = 48p
-38 + 48p = 10 + -8p + 8p

Combine like terms: -8p + 8p = 0
-38 + 48p = 10 + 0
-38 + 48p = 10

Add '38' to each side of the equation.
-38 + 38 + 48p = 10 + 38

Combine like terms: -38 + 38 = 0
0 + 48p = 10 + 38
48p = 10 + 38

Combine like terms: 10 + 38 = 48
48p = 48

Divide each side by '48'.
p = 1

Simplifying
p = 1

See similar equations:

| 15u-9u=30 | | 4(3x+5)-6(3x-5)=11x+3(2x-7) | | 10y+10=5y+20 | | 18=24-3w | | 4=2v-10 | | 16+2u=56 | | 0.4x+0.96=2.96 | | X^2=7/4 | | -17/5= | | 13f+8=19f-17f-3 | | 120-40/7-5=x | | 3b+4=b+19 | | 4e-8=19 | | 4x-9=3(x+5) | | 4a=8-5a | | 7-16m=-20m-17 | | 0.9-0.45= | | 5=17-4n | | 4y+3=6y+8 | | 83-v=274 | | 8.2x-57.4=-24.6 | | 10v+5v=25 | | 15n-25n+8n=18 | | 4g-13=3 | | 3(4z+9)=20-7z | | 24-c=2(3) | | 8y-5y=-27 | | -12n-12=-11n | | (-4v+3)(8v+6)=0 | | 9400=10 | | 9y-4y-14=48.80 | | 8.2x-53.4=-24.6 |

Equations solver categories